Kabuki Syndrome and Anorectal Malformations: Implications for Diagnosis and Treatment - Sotirios Siminas; Colin Tennant Baillie; Richard Turnock (Georg Thieme Verlag KG, 2015)
Abstract Kabuki syndrome (KS) is a rare genetic condition characterized by a distinctive facies, intellectual disability, growth delay, and a variety of skeletal, visceral, and other anomalies, including anorectal malformations (ARMs). We present two cases of female patients with KS, diagnosed and successfully managed at our institution, one with a perineal fistula and one with a rectovestibular fistula. Our report, along with a literature review, shows that the syndrome is usually associated with "low" anomalies, with a potential for a good prognosis. Management of the anorectal anomaly in patients with KS is not essentially different from that in other nonsyndromic patients, taking into account the frequent association of the syndrome with serious congenital heart disease, which might affect the decision-making and timing of the stages of anorectal reconstruction. The frequent occurrence of learning and feeding difficulties makes establishment of toilet training and bowel management rather more challenging, requiring the expertise of a multidisciplinary team. The finding of ARMs in female patients with other characteristics of KS, although inconstant, could support the clinical suspicion for the syndrome until genetic confirmation is available, and should alert the physician for the potential of severe cardiac defects.